Socioeconomic inequalities in physical activity among older adults before and during the COVID-19 pandemic: evidence from the English Longitudinal Study of Ageing - Nick P Townsend; Olivia S Malkowski; Mark J Kelson; Charlie E M Foster; Max J Western (BMJ Publishing Group, 2023)
Introduction The influence of the COVID-19 pandemic on physical activity behaviour in older adults is of particular concern. However, little is yet known about how pre-existing socioeconomic inequalities in older adults' physical activity have been affected by the COVID-19 pandemic. The aim of this study was to explore socioeconomic disparities in physical activity levels and change over time among older adults in England, using data collected before and during the COVID-19 pandemic.Methods This longitudinal cohort study analysed data from 3720 older adults (aged 60+ years) who participated in wave 9 (2018/2019) of the main English Longitudinal Study of Ageing (ELSA) survey and wave 2 of the ELSA COVID-19 substudy (November/December 2020). Using multilevel ordinal logistic models, we investigated associations between socioeconomic variables (education, occupational class and wealth) and physical activity, adjusting for potential confounders. We also examined interactions between socioeconomic variables and time (prepandemic vs intrapandemic) to investigate changes in the magnitude of inequalities in physical activity across the two survey periods.Results The proportion of participants considered 'inactive' rose from 5.7% before the COVID-19 pandemic to 12.5% in November and December 2020. Higher education, occupational class and wealth were positively associated with physical activity before the lockdown. These socioeconomic disparities generally persisted during the COVID-19 pandemic. There was some evidence that differences in physical activity based on education and occupational class reduced during the COVID-19 pandemic, relative to prepandemic data. However, these associations were no longer statistically significant when the three socioeconomic variables and their interactions with time corrected for one another (p>0.05).Conclusion Our results suggest there was no additional influence of the COVID-19 pandemic on pre-existing socioeconomic inequalities in older adults' physical activity levels.